Investigating palaeodietary and social differences between two differentiated sectors of a Neolithic community, La Bòbila Madurell-Can Gambús (north-east Iberian Peninsula). (September 2015) - Fontanals-Coll, Maria; Subirà, M. Eulàlia; Bonilla, Marta Díaz-Zorita; Duboscq, Stephanie; Gibaja, Juan F.
Abstract: This palaeodietary study presents new carbon and nitrogen isotope data for human and animal skeletal remains from the Middle Neolithic necropolis of Bòbila Madurell–Can Gambús (Vallès Occidental, Spain). The necropolis is divided into two sectors, Bòbila Madurell and Can Gambús, which differ in terms of their demography and the wealth of their tombs. This study examines each sector separately in order to assess how far these demographic and grave good differences also correspond to diversity in the community. The results show that a diet based on C3 terrestrial resources is found homogeneously in both sectors of the community. The protein component of the diet consisted mainly of meat, milk and other dairy products from livestock as well as C3 plant protein from the typical cereals and legumes grown in this period. The results also show the existence of slight intra-population sex and age differences in the Can Gambús sector, while these are not perceptible in the Bòbila Madurell sector. This allows inferences not only about the diet of the Neolithic communities that lived in the north-east of the Iberian Peninsula but also about their customs, which would be reflected in social differentiation as regards the consumption of certain kinds of food. These are important data that can be added in future studies of socio-economic patterns in Neolithic societies in the rest of Europe. Highlights: We report new dietary isotope analysis from NE Iberian Peninsula Neolithic sites. NE Iberian Peninsula groups had a diet composed mainly of C3 terrestrial resources. These groups had an economy based equally in farming and herding. The data support a reduced use of marine and freshwater resources in the Neolithic. This study shows evidence of slight intra-population gender and age differences.